'A Mile Wide and an Inch Deep': Surveys of Public Attitudes towards Development Aid. (1st January 2012) - Hudson, David; vanHeerde-Hudson, Jennifer
In this article we argue that existing survey instruments used to examine public attitudes to global poverty are not fit for purpose. Surveys need to be redesigned to successfully support the threefold purpose of development education and public engagement. The core of our critique is that existing measures suffer from poor measurement validity, and fail to control for knowledge-levels or perceptions of aid effectiveness, both of which are thought to limit support. Researchers also lack understanding of the factors that motivate support for development aid in the first place. We conclude by making recommendations for future surveys of public attitudes and suggest that building support for development may require speaking to many publics as opposed the public.